AUTONOMY POLICY AND SOCIAL WELFARE IN TANGERANG CITY - Pitri Yandri (Economic Journal of Emerging Markets, 2012)
The paper analyzes the effect of public expenditure and the implementation of local autonomy policy on Human Development Index (HDI). The paper uses Principal Component Regression Analysis to conduct the analysis. The result shows that public expenditure has a positive effect on HDI. It also finds that the increase in HDI is bigger post the implementation of local autonomy policy. The elasticity of each coefficient of public expenditure are as follows: 1.58 for agriculture sector; 0.94 for education sector; 0.36 for health sector; 0.44 for housing sector; 0.61for infrastructure sector, and 0.70 for GRDP. Keywords: Public expenditure, Human Development Index, principal component analysisJEL classification numbers: H40, H52, I21, I32AbstrakPenelitian ini mengkaji pengaruh belanja publik dan pelaksanaan otonomi daerah terhadap tingkat Indeks Pembangunan Manusia (IPM) di Kota Tangerang. Penelitian ini mengaplikasikan Analisis Regresi Komponen Utama untuk melakukan analisis. Hasil uji menunjukkan bahwa belanja publik memiliki pengaruh yang positif terhadap IPM. Lebih jauh, peningkatan IPM tersebut semakin besar setelah pelaksanaan kebijakan otonomi daerah. Penelitian ini juga menemukan tingkat elastisitas per sektor terhadap belanja publik sebagai berikut: 1.58 pada sektor pertanian; 0.94 pada sektor pendidikan; 0.36 sektor kesehatan, 0.44 pada sektor perumahan; 0.61 pada sektor infrastruktur, dan 0.77 untuk PDRB.Keywords: Belanja publik, Indeks Pembangunan Manusia, analisis regresi komponen utamaJEL classification numbers: H40, H52, I21, I32